Getting to implementation: Adaptation of an implementation playbook - Yakovchenko, Vera; Rogal, Shari S.; Goodrich, David E.; Lamorte, Carolyn; Neely, Brittney; Merante, Monica; Gibson, Sandra; Scott, Dawn; McCurdy, Heather; Nobbe, Anna; Morgan, Timothy R.; Chinman, Matthew J. (Frontiers in Public Health, 2023)
Introduction Implementation strategies supporting the translation of evidence into practice need to be tailored and adapted for maximum effectiveness, yet the field of adapting implementation strategies remains nascent. We aimed to adapt “Getting To Outcomes”® (GTO), a 10-step implementation playbook designed to help community-based organizations plan and evaluate behavioral health programs, into “Getting To Implementation” (GTI) to support the selection, tailoring, and use of implementation strategies in health care settings. Methods Our embedded evaluation team partnered with operations, external facilitators, and site implementers to employ participatory methods to co-design and adapt GTO for Veterans Health Administration (VA) outpatient cirrhosis care improvement. The Framework for Reporting Adaptations and Modifications to Evidenced-based Implementation Strategies (FRAME-IS) guided documentation and analysis of changes made pre- and post-implementation of GTI at 12 VA medical centers. Data from multiple sources (interviews, observation, content analysis, and fidelity tracking) were triangulated and analyzed using rapid techniques over a 3-year period. Results Adaptations during pre-implementation were planned, proactive, and focused on context and content to improve acceptability, appropriateness, and feasibility of the GTI playbook. Modifications during and after implementation were unplanned and reactive, concentrating on adoption, fidelity, and sustainability. All changes were collaboratively developed, fidelity consistent at the level of the facilitator and/or implementer. Conclusion GTO was initially adapted to GTI to support health care teams' selection and use of implementation strategies for improving guideline-concordant medical care. GTI required ongoing modification, particularly in steps regarding team building, context assessment, strategy selection, and sustainability due to difficulties with step clarity and progression. This work also highlights the challenges in pragmatic approaches to collecting and synthesizing implementation, fidelity, and adaptation data. Trial registration This study was registered on ClinicalTrials.gov (Identifier: NCT04178096).